The application status of midline catheter in the transfusion treatment (中线导管在输液治疗中的应用现状) - LUO Lingyun (骆凌云); ZHU Caihong (朱彩红); YANG Hongyan (杨红艳) (中西医结合护理)
This paper summarized the changes in materials, range of application, indwelling time, catheterization methods and complications of midline catheter, in order to carry out homogenized nursing according to the guidelines, reduce the occurrence of complication of midline catheter and ensure the safety of infusion for patients. (本文概述中线导管(MC)的材质变化、适用范围、留置时间、置管方式及并发症的情况, 以期以指南为标准开展同质化护理, 减少中线导管并发症发生风险, 保障患者输液安全。)